Association of household socioeconomic status, neighborhood support system and adherence to dietary recommendation among persons with T2DM, a facility-based cross-sectional study in Ghana - Be-Ikuu Dominic Doglikuu; Abdulai Abubakari; Mehdi Yaseri; Elham Shakibazadeh; Abolghassem Djazayery; Khadijeh Mirzaei (BMC, 2021)
Abstract Background Dietary recommendation help persons with diabetes adopt to healthy eating habits to achieve optimal glycemic control. Socioeconomic-status and neighborhood support system can influence adherence to dietary recommendation. The purpose of our study is to assess the association of household-socioeconomic status and neighborhood-support system with adherence to dietary recommendation among persons with type 2 diabetes mellitus (T2DM). Methods Facility-based cross-sectional-survey was conducted in Brong Ahafo region, Ghana. Six hospitals were randomly selected and 530 individuals with T2DM consecutively recruited from the selected hospitals for the study. Structured-questionnaires were used to collect socio-demographic variables. Adherence to dietary-recommendation was the outcome-variable, and was assessed using perceived dietary-adherence questionnaire. Results Age (years) (P-value = 0.005), Physical-Activity level (P-value = 0.024) Receive-moderate Social-Support (P-value = 0.004) and High-Socioeconomic status (P-value = 0.046) were significantly correlated with adherence to dietary-recommendation. Age (years) regression coefficient (β) -0.089, 95%CI (− 0.12, − 0.001), Being married β0.103, 95%CI (0.002, 0.02), moderate and low-social support system β 0.309, 95%CI (0.17, 0.38) and β-0.192, 95%CI (− 0.26, − 0.06) respectively, and high-socioeconomic status β 0.197, 95%CI (0.06, 0.25) were significantly associated with adherence to dietary-recommendation. Conclusion Social-support system and socioeconomic-status could be associated with adherence to dietary-recommendation. Therefore, health workers should consider patients' social support system and socioeconomic status as modifiable factors for optimum adherence.